2021
DOI: 10.3390/jof7040269
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Outcomes of Non-albicans Candida Bloodstream Infection in Patients with Candidemia at Siriraj Hospital—Thailand’s Largest National Tertiary Referral Hospital

Abstract: This study aimed to investigate the risk factors for and the outcomes of patients with candidemia caused by non-albicans Candida. Candidemia patients treated at Siriraj Hospital (Bangkok, Thailand) during January 2016 to December 2017 were enrolled. A total of 156 patients (mean age: 65 years, 56.4% male) were included. The most prevalent underlying conditions were diabetes (32.1%), chronic cardiac disease (28.2%), chronic kidney disease (26.9%), and hematologic malignancies (21.2%). Candida species isolated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 18 publications
2
32
0
Order By: Relevance
“…Consistent with our previous studies [ 18 , 32 ], resistance to antifungal drugs among bloodstream C. albicans and C. tropicalis isolates was rare as only 1 of 74 C. albicans isolates exhibited in vitro resistance to fluconazole and voriconazole only. While the rate of resistance to fluconazole among C. albicans isolates in Kuwait is comparable to the worldwide data, fluconazole resistance among global C. tropicalis isolates is more common, particularly among isolates from east/southeast Asian countries [ 8 , 14 , 67 ]. The only triazole-resistant C. albicans isolate (Kw150/8/18) detected in this study contained two nonsynonymous (T123I and Y132H) mutations in ERG11, which are well-known to confer resistance of C. albicans to fluconazole [ 72 ].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Consistent with our previous studies [ 18 , 32 ], resistance to antifungal drugs among bloodstream C. albicans and C. tropicalis isolates was rare as only 1 of 74 C. albicans isolates exhibited in vitro resistance to fluconazole and voriconazole only. While the rate of resistance to fluconazole among C. albicans isolates in Kuwait is comparable to the worldwide data, fluconazole resistance among global C. tropicalis isolates is more common, particularly among isolates from east/southeast Asian countries [ 8 , 14 , 67 ]. The only triazole-resistant C. albicans isolate (Kw150/8/18) detected in this study contained two nonsynonymous (T123I and Y132H) mutations in ERG11, which are well-known to confer resistance of C. albicans to fluconazole [ 72 ].…”
Section: Discussionmentioning
confidence: 74%
“…The second most common Candida species isolated from patients with invasive candidiasis varies with geographical locations and is identified as C. parapsilosis in Latin/South America and many European and Middle Eastern countries, or as C. glabrata in North America, or as C. tropicalis in east/southeast Asian countries [ 8 , 14 , 23 , 24 , 65 ]. More recent studies have shown that C. tropicalis has now surpassed C. albicans as the predominant Candida species among candidemia patients in some south-southeast Asian countries [ 8 , 66 , 67 ]. An important finding of our study was the emergence of C. auris as the fourth most common Candida species isolated from candidemia patients, replacing C. glabrata and its emergence as the predominant species in two major (Al-Sabah and Farwaniya) hospitals in Kuwait.…”
Section: Discussionmentioning
confidence: 99%
“…Candidemia is a leading cause of fungal infections among neonates and infants, and it also affects immunocompromised adults ( Golan et al, 2005 ; Mantadakis et al, 2018 ). The incidence of candidemia is 13.3 per 100,000 people, and the mortality ranges from 36 to 50% ( Ngamchokwathana et al, 2021 ). Given the rapid and fatal course of candidemia, timely and effective treatment depends on rapid and accurate diagnosis of this invasive fungal infection ( Pfaller and Diekema, 2007 ; Schroeder et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several species of Candida can cause infections, being C. albicans the most prevalent species in humans [4,5]. However, C. glabrata, C. parapsilosis, C. tropicalis, and C. krusei, which are all known as non-albicans Candida species, have also been isolated in invasive infections [6], mainly from renal transplant recipients [7] and candidemia caused by these non-albicans Candida species was associated with underlying conditions such as chronic kidney disease [8]. In this regard, C. tropicalis was isolated from systemic infections all over the world, being the second most prevalent yeast in Brazil and the third in South America [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%